Determinan Pengelolaan Keuangan UKM di Kecamatan Aikmel Kabupaten Lombok Timur - Zaen Zaenuri, Ahmad; Sulkiah, Sulkiah (E-Jurnal Akuntansi, 2025)
The purpose of this study was to analyze the effect of the influence of organizational commitment, accounting information systems, HR competencies, and marketing digitalization on the financial management of SMEs in Aikmel District, East Lombok Regency. The research method used is a survey method with a questionnaire of 75 respondents, namely SMEs in Aikmel District, East Lombok. The results of this study indicate that organizational commitment has a positive effect on financial management, accounting information systems have no effect on financial management, human resource competencies have a positive effect on financial management, and marketing digitalization has a positive effect on financial management. Keywords:  Organizational commitment; accounting information systems ;   HR competencies, Marketing Digitalization;   UKM F inancial Management.